2020
DOI: 10.1111/eea.12877
|View full text |Cite
|
Sign up to set email alerts
|

Attacks by predators on artificial cryptic and aposematic insect larvae

Abstract: Colour and colour patterns seem to be especially important visual warning signals for predators, which might have innate or learned ability to avoid aposematic prey. To test the importance of larval colour pattern of the aposematic ladybird Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), an invasive alien species in Europe, we presented the plasticine models of aposematic larvae to wild and naïve birds. We studied the attacks on aposematic larvae of various patterns and colours in nature and in an outd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…In fact, when looking at predation rates at the peak season in our system (23%-24% in spring and 20%-25% in autumn) we find values that are well within the range observed in other ecosystems . Moreover, the overall daily predation rate recorded in the tree canopy of Vachellia F I G U R E 4 Observed vertebrate predation rates (mean ± 95% CI, n = 120 caterpillars per position during each sampling event) on Vachellia trees at ground and canopy levels in Evrona Nature Reserve, southern Israel, between November 2018 and October 2019 trees (8.9%) was higher than the predation rates registered in temperate regions (Aslam et al, 2020;Barbaro et al, 2012;Bereczki et al, 2015;Gunnarsson et al, 2018;Low et al, 2014a;Zverev et al, 2020), although lower than in most tropical forests (Denan et al, 2020;Liu et al, 2020;. This may be explained by Vachellia being the only trees present in this ecosystem and therefore an important habitat for arthropods (Nothers et al, 2017), leading to high predation rates relative to some of the plants sampled in other ecosystems.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, when looking at predation rates at the peak season in our system (23%-24% in spring and 20%-25% in autumn) we find values that are well within the range observed in other ecosystems . Moreover, the overall daily predation rate recorded in the tree canopy of Vachellia F I G U R E 4 Observed vertebrate predation rates (mean ± 95% CI, n = 120 caterpillars per position during each sampling event) on Vachellia trees at ground and canopy levels in Evrona Nature Reserve, southern Israel, between November 2018 and October 2019 trees (8.9%) was higher than the predation rates registered in temperate regions (Aslam et al, 2020;Barbaro et al, 2012;Bereczki et al, 2015;Gunnarsson et al, 2018;Low et al, 2014a;Zverev et al, 2020), although lower than in most tropical forests (Denan et al, 2020;Liu et al, 2020;. This may be explained by Vachellia being the only trees present in this ecosystem and therefore an important habitat for arthropods (Nothers et al, 2017), leading to high predation rates relative to some of the plants sampled in other ecosystems.…”
Section: Discussionmentioning
confidence: 88%
“…Our study has added to the limited knowledge on the relative efficacy of two major strategies of two types of adaptive coloration that reduce the risk of predation. Some earlier experiments showed better survival of natural aposematic prey compared with cryptic prey (Sillén-Tullberg 1985 ; Aslam et al 2020 ), but the relative efficacy of cryptic and aposematic colouration may depend on the environment (Seymoure et al 2018 ). We found that the relative efficacy of these two strategies also depends on the composition of the bird community with respect to the naïvety level.…”
Section: Discussionmentioning
confidence: 99%
“…Both red and yellow are long-wavelength colours, which are known to provide effective aposematic signals (Stevens and Ruxton 2012 ). Green is a typical cryptic colour for herbivorous insects (Aslam et al 2020 ), while black may be considered differently. In some experiments, black food was least preferred by chicks (Roper and Marples 1997 ), but we follow studies using plasticine models in natural conditions (Mappes et al 2014 ; Zvereva et al 2019 ) which considered black as cryptic colour.…”
Section: Methodsmentioning
confidence: 99%
“…Larvae and pupae of this species may also be aposematically coloured, combining black and orange (Nedvěd, ), but little is known about their toxicity or predator responses to them. Artificial larvae resembling H. axyridis were attacked much less often than green or black dummies (Aslam et al ., ).…”
Section: Introductionmentioning
confidence: 97%